2017
DOI: 10.1371/journal.pntd.0005976
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus dissemination from the midgut of Aedes aegypti is associated with temporal basal lamina degradation during bloodmeal digestion

Abstract: In the mosquito, the midgut epithelium is the initial tissue to become infected with an arthropod-borne virus (arbovirus) that has been acquired from a vertebrate host along with a viremic bloodmeal. Following its replication in midgut epithelial cells, the virus needs to exit the midgut and infect secondary tissues including the salivary glands before it can be transmitted to another vertebrate host. The viral exit mechanism from the midgut, the midgut escape barrier (MEB), is poorly understood although it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 55 publications
(92 reference statements)
5
106
0
Order By: Relevance
“…To examine if an additional blood- or protein-meal could influence the integrity of the basal lamina, we utilized a collagen hybridizing peptide (CHP) that specifically binds unfolded collagen chains, to serve as an indicator of tissue damage (Hwang et al, 2017). Collagen IV serves as a primary component of the midgut basal lamina (Arrighi and Hurd, 2002; Arrighi et al, 2005; Dong et al, 2017) that becomes degraded following blood-feeding (Dong et al, 2017). We demonstrate that CHP stains dissected midguts shortly after blood-or protein-feeding (Figure 2A), with the intensity of CHP staining reaching peak levels ∼18hr after blood- (Figure 2B) or protein-feeding (Figure 2C), before being repaired shortly thereafter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine if an additional blood- or protein-meal could influence the integrity of the basal lamina, we utilized a collagen hybridizing peptide (CHP) that specifically binds unfolded collagen chains, to serve as an indicator of tissue damage (Hwang et al, 2017). Collagen IV serves as a primary component of the midgut basal lamina (Arrighi and Hurd, 2002; Arrighi et al, 2005; Dong et al, 2017) that becomes degraded following blood-feeding (Dong et al, 2017). We demonstrate that CHP stains dissected midguts shortly after blood-or protein-feeding (Figure 2A), with the intensity of CHP staining reaching peak levels ∼18hr after blood- (Figure 2B) or protein-feeding (Figure 2C), before being repaired shortly thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the effects of P. berghei killing are independent of the host blood meal, and more likely caused by the distention of the mosquito midgut following feeding. Ingestion of a blood- or protein-meal results in dramatic changes to midgut epithelium cell morphology, causing a flattening of the columnar cells, the loss of microvilli, and substantial degradation of the basal lamina (Dong et al, 2017; Sodja et al, 2007). This agrees with our CHP assays demonstrating the presence of degraded collagen shortly after taking a blood- or protein-meal, suggesting that the integrity of the basal lamina is compromised during distention, enabling the exposure of developing oocysts to components of the mosquito hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/246306 doi: bioRxiv preprint first posted online Jan. 10, 2018; 4 midgut, apoptosis and regeneration of midgut epithelial cells, and altered permeability of the basal lamina layer-that could enhance or accelerate virus dissemination out of the midgut 20,21 .…”
Section: Main Textmentioning
confidence: 99%
“…The basal lamina layer surrounding the midgut epithelium represents a physical barrier that is impermeable to virus particles 26 , yet viruses are still able to escape from the gut. While a second non-infectious bloodmeal is not required for escape, a recent study showed that the integrity of the basal lamina was compromised 24-32 hours post-bloodmeal coincident with increased collagenase activity 21 . Future studies are needed to identify mechanisms mediating arbovirus escape from the midgut and how multiple bloodmeals enhance this event.…”
mentioning
confidence: 99%
“…During the extrinsic incubation period (EIP), a virus that enters the mosquito midgut and is able to pass into the hemolymph may infect fat body cells, trachea, hemocytes, ovaries, nerve tissue, and reach salivary glands [2, 18, 32, 33]. For an arbovirus to be transmitted to a new vertebrate host in a subsequent blood meal, it must first be secreted with the saliva by the acinar (epithelial) cells to the luminal side of the salivary glands.…”
Section: Infection Of a Aegypti Mosquitoesmentioning
confidence: 99%